Questioning the Legality and Effectiveness of Economic Sanctions in International Law - Cenk Keskin (Public and Private International Law Bulletin)
The international community is organized horizontally. There is no hierarchically superior institution in the relations prescribed among equals, and rules are formed in the direction of common interests; thus, the legal order pertaining to the international community differs from classical municipal legal orders. Effective compliance with rules is ensured in proportion to the parallels of mutual interests in the international order. An increase has been observed in cooperation particularly with the increase of interdependencies due to globalization. Violating the rules of international law creates a responsibility for that state. Individual and collective means of enforcing a state to comply with international rules are observed to exist. However, despite any warning to comply with international law, some actors in this community continue to be in violation and insist on exhibiting illegal behaviors. Economic sanctions and countermeasures applied on the basis of erga omnes obligations do not yet grant the same rights as an injured state to third-party states that have not been directly harmed by an unlawful act. However, developments in the Russia-Ukraine war have brought forth a new perspective to international law. Economic sanctions have become increasingly popular as a form of sanction and within themselves also possess a rich variety. Some of these diverse sanctions are not as effective as was assumed and also lack legal support. Some economic sanctions with a long prior history have been observed to result in harsher outcomes than the use of force based on their effects and to also affect a largely innocent population instead of the perpetrators of the violations. The legal regime of effective economic sanctions that directly aim for results is currently taking shape against the perpetrators of unlawful behavior.